Medieval Symbols in "The Name of the Rose", by Umberto Eco - Paula Onofrei (Anastasis: Research in Medieval Culture and Art, 2018)
The purpose of the present article is to identify and analyze some of the medieval symbols present in the novel The Name of the Rose, written by Umberto Eco, insisting on their importance. Combining elements of a historical romance, a thriller and a novel of ideas, Umberto Eco manages to create a vivid, intertextual book who is filled with mysteries, intriguing the reader from the beginning to the end.